P-005 Anesthetic considerations and the role of blood pressure management in the endovascular treatment of acute ischemic stroke. (16th November 2010) - Menon, B; Davis, M; Herrera, C; Eesa, M; Demchuk, A; Goyal, M; Archer, D; Hill, M
Abstract : Introduction: Increasingly used in North America, endovascular thrombolysis for ischemic stroke results in high recanalization rates without a comparable increase in good clinical outcomes. Many neurointerventionalists prefer general anesthesia to keep patients still. The purpose of this study is to identify the role of anesthesia and any other associated periprocedural factors in determining clinical outcomes in patients undergoing endovascular procedures for acute ischemic stroke. Methods: We retrospectively studied patients who underwent open label intra-arterial procedures for stroke from 2003 to 2009 in our intra-arterial database. Data were collected from chart reviews and automated anesthesia records. We used the Houston Intra-arterial Therapy (HIAT) score (1 point for age >75 years; 1 for National Institutes of Health Stroke Scale (NIHSS) score >18 and 1 point for glucose >150 mg/dl) for adjusting for baseline differences. The primary clinical outcome was modified Rankin Scale 0–2 at 3 months. Results: 96 patients (67 males, median age 65 years) with median NIHSS 17 (range 12–20) were included in the study. The distribution of type of anesthesia was as follows: 48/96 general anesthesia, 44/96 conscious sedation (14) or local anesthesia only (30), and 4/96 undetermined. 7/48 (15%) in the general anesthesia group had good clinical outcome compared with 29/44 (66%) in the local anesthesia/conscious sedation group (RR 0.22; 95% CI 0.11 to 0.45). After adjusting for HIAT score and the presence or absence of any major anesthetic comorbidities, the general anesthesia group had significantly worse clinical outcome (p=0.001). Lower blood pressure correlated with poorer clinical outcomes in both anesthesia groups. The lowest mean systolic blood pressure in the general anesthesia group was 104 mm Hg compared with 135 mm Hg in the local anesthesia/conscious sedation group (p=0.0001). Conclusion: The use of general anesthesia during endovascular procedures in acute ischemic strokes is associated with poorer clinical outcomes at 3 months. This could be because of lower periprocedural blood pressures.